Integrating Developmental Supervision and School Culture to Foster Teacher Professional Growth - Umniatuz Zahro (Kognisi: Jurnal Ilmu Keguruan, 2025)
This study investigates the implementation of developmental supervision by the principal in enhancing teacher professionalism at SMP Birrul Ummah Tegalrejo. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that developmental supervision plays a strategic role in improving educational quality by functioning not merely as control but as continuous professional guidance. Effective supervision, when carried out in a planned, need-based, and collaborative manner, fosters teachers’ pedagogical, professional, social, and personal competencies. The results also highlight the importance of a positive school culture, reflective practices, and the principal’s role as both mentor and facilitator in creating an environment conducive to professional growth. Furthermore, developmental supervision encourages instructional innovation, the use of interactive learning media, and contributes to enhancing teachers’ motivation as well as students’ learning outcomes. Overall, this study underscores that developmental supervision integrated with teacher professional development empowers teachers to optimize their potential and supports the creation of high-quality learning.